Tinjauan Yuridis Dogmatis terhadap Kedudukan Keadilan Restoratif sebagai Alasan Penghapus Pidana dalam Sistem Pemidanaan Indonesia - Yulianis Safrinadiya Rahman; Rolly Muliazi; Lutfi Yusup Rahmathoni (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The enactment of Law Number 1 of 2023 on the Criminal Code and Law Number 20 of 2025 on the Criminal Procedure Code elevates restorative justice into statutory law, raising questions regarding its position within the doctrine of grounds for excluding criminal liability. This normative legal research employs statutory, conceptual and analytical approaches. The findings indicate that restorative justice satisfies neither justificatory nor excusatory grounds because it does not eliminate the unlawfulness of the act or the offender’s culpability. The study concludes that restorative justice is more appropriately classified as a procedural, opportunistic ground for excluding prosecution, contributing to the reform of Indonesia’s criminal law system.